Vasopressin potentiates mineralocorticoid selectivity by stimulating 11 beta hydroxysteroid deshydrogenase in rat collecting duct. - Alfaidy, N (1997)
Arginine vasopressin (AVP) and corticosteroid hormones are involved in sodium reabsorption regulation in the renal collecting duct. Synergy between AVP and aldosterone has been well documented, although its mechanism remains unclear. Both aldosterone and glucocorticoid hormones bind to the mineralocorticoid receptor (MR), and mineralocorticoid selectivity depends on the MR-protecting enzyme 11 beta hydroxysteroid deshydrogenase (11-HSD), which metabolizes glucocorticoids into derivatives with low affinity for MR. We have investigated whether the activity of 11-HSD could be influenced by AVP and corticosteroid hormones. This study shows that in isolated rat renal collecting ducts, AVP increases 11-HSD catalytic activity. This effect is maximal at 10(-8) M AVP (a concentration clearly above the normal physiological range of AVP concentrations) and involves the V2 receptor pathway, while activation of protein kinase C or changes in intracellular calcium are ineffective. The stimulatory effect of AVP on 11-HSD is largely reduced after adrenalectomy, and is selectively restored by infusion of aldosterone, not glucocorticoids. We conclude that this synergy between AVP and aldosterone in controlling the activity of 11-HSD is likely to play a pivotal role in resetting mineralocorticoid selectivity, and hence sodium reabsorption capacities of the renal collecting duct.